STUDENTS’ ERRORS IN USING MODALS - Enni Maisaroh (Universitas Potensi Utama, 2018)
This study deals with the students’ errors in using modals of Can, May and Must. There were 25 students chosen as the sample who were asked to write compositions containing the modals. There were errors found in the writings which were categorized into 10 types according to the use of the modals. Type 1 (modal + simple infinitive to) is the dominant errors while Type 5 ( modal + pronoun) is the fewest. In all, there were 52 errors made in 192 modals used. Therefore, the percentage of the errors is 27%. This implies that the students could use the modals quite well. The second most difficult in the compositions is Must (34.92%) while according to their responses in the questionnaire the most difficult modal verb is May (48%) the causes of the errors were that the students lacked the knowledge of the uses; They seldom, practiced the use of the modals in compositions , and applied translation approach to use the modals in their writings. It is suggested that they be taught the pattern modal + simple infinitive to because this is the most common error.